Robin and the making of American adolescence - O'Connor, Lauren R. (Comics culture., 2021)
Holy adolescence, Batman! Robin and the Making of American Adolescence offers the first character history and analysis of the most famous superhero sidekick, Robin. Debuting just a few months after Batman himself, Robin has been an integral part of the Dark Knight's history--and debuting just a few months prior to the word "teenager" first appearing in print, Robin has from the outset both reflected and reinforced particular images of American adolescence. Closely reading several characters who have "played" Robin over the past eighty years, Robin and the Making of American Adolescence reveals the Boy (and sometimes Girl!) Wonder as a complex figure through whom mainstream culture has addressed anxieties about adolescents in relation to sexuality, gender, and race. This book partners up comics studies and adolescent studies as a new Dynamic Duo, following Robin as he swings alongside the ever-changing American teenager and finally shining the Bat-signal on the latter half of "Batman and--."